Population Dynamics of the Sea Slug Plakobranchus ocellatus (Opisthobranch: Sacoglossa: Elysioidea) on a Subtropical Coral Reef off Okinawa-jima Island, Ryukyu Archipelago, Japan - Tanamura, Daisuke (Zool Stud, 2016)
Daisuke Tanamura and Euichi Hirose (2016) Plakobranchus ocellatus is a sacoglossan sea slug that can retain functional chloroplast from its algal food. This species feed on multiple species of siphonous green algae and can survive several months without food by utilizing retained chloroplasts in its digestive gland (kleptoplasty). While the population dynamics of opisthobranchs are often influenced by the seasonal fluctuation of the abundance of food resources, the fluctuation of food availability would not be a crucial factor to restrict the occurrence of P. ocellatus. We monitored the population density of P. ocellatus for 20 months on a subtropical coral reef where the water temperature fluctuated from 17°C to 32°C, in order to examine whether the population density, distribution pattern of individuals, and size distribution of P. ocellatus are stable or seasonally change. The present results showed that P. ocellatus appeared all year round in the study site, while the population density changed seasonally. The population density decreased in cold (≤ 21°C) and hot (≥ 27°C) periods, and densities in the months of intermediate temperature range (< 21°C, > 25°C) were significantly higher than the densities in other months (Student’s t-test, P < 0.0001). Accordingly, population density is probably influenced by water temperature. Morisita’s Iδ indicated that the sea slugs were distributed in random patterns (13 months) or clumped patterns (7 months). Our field observations indicated that the sea slugs do not feed in daytime, and probably feed at night. Whereas P. ocellatus individuals of less than 10 mm were rarely recorded in the monitoring area, a decrease of the average body length and increase in population density in April – May suggest active recruitment of small individuals in this period.